Annual Report 2022: Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is a project administered by the Alliance of Bioversity International and the International Centre for Tropical Agriculture (CIAT). Momentum built during2022 demonstrates the continuing catalytic role of AICCRA in strengthening the agriculture research architecture in Africa. Activities financed under AICCRA are undertaken by a broad coalition of CGIAR partners working at continental, regional, and national levels. During 2022, the project reached2.9 million beneficiaries with enhanced climate information services (CIS) and/or validated climate-smart agriculture (CSA) technologies. Of these, 1.9million were reached via mass media broadcasting in Kenya. AICCRA country, regional, and thematic clusters made notable progress in reaching indicator targets for AICCRA’s Project Development Objectives and Intermediate Performance Indicators. Indeed, targets have been surpassed for 2022, with higher-than-expected outcomes achieved through effective collaboration and capacity building activities fostered through key partnerships established under AICCRA, with partners delivering at a greater pace than anticipated and delivering a broader set of outputs.